Gate-controlled multi-bit nonvolatile ferroelectric organic transistor memory on paper substrates. Issue 43 (18th October 2019) - Xu, Meili; Zhang, Xindong; Li, Shizhang; Xu, Ting; Xie, Wenfa; Wang, Wei
Abstract : A high-performance multi-bit organic transistor nonvolatile-memory, with good mechanical durability and environmental stability, was prepared for the first time on a paper substrate. Abstract : Paper substrate based organic field-effect transistor (OFET) nonvolatile memories (NVMs) not only exhibit many advantages such as being low-cost, biodegradable and renewable, but also hold promise for novel application as single-use and disposable NVMs for storing personal health statuses in daily life and providing good privacy protection by offering easy physical destruction in the technology of the internet of everything. This study demonstrates a facile method to realize a multi-bit OFET-nonvolatile memory (NVM) on an ordinary commercial paper substrate by designing and fabricating a multilayer ferroelectric gate dielectric, by which both the mobility and controllability of the remnant polarization depending on the gate voltages are greatly improved. The multi-bit OFET-NVMs on a paper substrate show excellent performances with a high mobility up to 0.92 cm −2 V −1 s −1, a distinct four-level reading I DS with a large memory margin of about one order of magnitude was achieved at low multi-level programming/erasing voltages (<40 V), and a reliable four-level switching endurance over 100 cycles and stable four-level data retention over 20 000 s was demonstrated. Additionally, the paper-based multi-bit OFET-NVMs exhibited a good mechanical bending durability and environmental stability against humidity, temperature, and air, indicating their potential application in flexible electronics. To the best of our knowledge, this is the first report of multi-bit OFET-NVMs on paper substrates.